The validation of the 2010 American Association for the Study of Liver Diseases guideline for the diagnosis of hepatocellular carcinoma in an endemic area. Issue 2 (February 2015) - Lin, Ming‐Tsung; Chang, Kuo‐Chin; Chou, Yeh‐Pin; Tseng, Po‐Lin; Yen, Yi‐Hao; Wang, Chih‐Chi; Tsai, Ming‐Chao; Cheng, Yu‐Fan; Eng, Hock‐Liew; Wu, Cheng‐Kung; Hu, Tsung‐Hui
Abstract Background and Aim Hepatocellular carcinoma (HCC) diagnosis could be made with one typical imaging study in a cirrhotic liver by the guideline of the American Association for the Study of Liver Diseases (AASLD) in 2010. Patients with hepatitis B who may not have fully developed cirrhosis could be applied. We aim to retrospectively analyze and validate the diagnostic power of the 2010 guideline in an HCC endemic area (Taiwan). Methods From January 2006 to December 2010, a total of 648 patients with liver tumor post‐surgical resection were reviewed. The fibrotic scores were verified by METAVIR score 4. Among the 648 patients, 569 (87.8%) were HCC patients. Hepatitis B accounts for 54.5%, hepatitis C 21.9%, hepatitis B + C 2.8%, and non‐hepatitis B or C 20.7% of patients. Two hundred eighty‐eight of 648 (44%) patients were with cirrhotic liver. Results The diagnostic sensitivity, specificity, positive predictive value (PPV), negative predictive value, and accuracy of the 2010 AASLD guideline f are 99.1%, 36.7%, 91.9%, 85.3%, and 91.5%, respectively. Cirrhotic liver exhibited a higher PPV (P < 0.001) but lower specificity (P = 0.0479) than non‐cirrhotic liver. In both cirrhotic and non‐cirrhotic condition, no difference existed in patients with hepatitis B or hepatitis C (P > 0.05). Conclusions Similar sensitivity of HCC diagnosis existed between cirrhotic and non‐cirrhotic liver, and across different fibrotic stages. But cirrhotic liver exhibited a higher PPV. Hepatitis B or C has no decisive effect in HCC diagnosis.